Enhancement in mineralization of a number of natural refractory organic compounds by the combined process of sonolysis and ozonolysis (US/O3) - Cui, M.; Jang, M.; Cho, S.H.; Elena, D.; Khim, J. (2011)
As an advanced oxidation process, the combination of sonolysis (US)/ozonolysis (O3) was investigated on the treatment of tannic acid (TA) and humic acid (HA). In this study, biodegradable chemicals were found by the molecular weight and GC-MS analysis method, and mineralization rate and synergetic effects were also studied. For the water samples prior to the treatment of US/O3, ratios of molecular size higher than 5000 and 2000 Da for HA and TA, detected by the ultra filtration method, were 90.25 and 89.53, respectively. However, after 0.5 h of reacting, this ratio rapidly reduced to 3 and 4, and the ratios of molecules for HA and TA less than 500 Da rapidly increased from 0.8 to 41 and from 0.65 to 39, respectively. In the results of chemical oxygen demand (CODCr) and total organic carbon (TOC) reductions, the US/O3 process also showed synergetic effect by US/O3 for CODCr of HA and TA were 19 and 11, and those for TOC of HA and TA were 0 and 1, respectively. The major by-products of the oxidation process included formaldehyde, acetone, hydroxylamine, etc. Biological decomposable materials could be indirectly inferred by measuring the molecular weights and intermediates. Â© 2010 Elsevier B.V.